IMPLEMENTASI MODEL KOOPERATIF TEAMS GAMES TOURNAMENT PADA PEMBELAJARAN SOSIOLOGI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS XII - Lisa Ranti Mardiyanti; Imran Imran; Iwan Ramadhan; Tri Wijaya (Jurnal Muara Pendidikan, 2023)
The purpose of this study was to see whether students learn better by using Classroom Action Research consisting of two cycles using the Kahoot-based teams' games tournament cooperative learning model with action research steps starting from planning, implementation, and evaluation. The research involved all students of class XII Sociology TL 8 at SMA Negeri 1 Pontianak, totaling 36 people. Using interactive learning media and models is one way to improve student learning outcomes. The results showed that the learning outcomes of XII Sociology TL 8 students could be improved by implementing the Kahoot-based tournament game team cooperative learning model. The results show that by implementing the Kahoot media-based TGT learning model, students' learning outcomes have increased. In cycles 1 and 2 there was an increase in the class average of 82.5 to 85.2. In learning outcomes, there was an increase of 63% to 81%. Thus there was a significant change after using the TGT learning model.